The Effect of Digital Marketing Strategies on Increasing Sales of Muslim Clothing at Moeslim House in Sukabumi - Amir, Miftah; Syahlan, Fatra; Berliana, Berliana; Purnamasari, Laely; Nugraha, Derry (Rangkiang: Journal of Islamic Economics and Business, 2024)
The rise of digital technology has transformed traditional marketing approaches, making digital marketing strategies crucial for business success. This study examines the effectiveness of various digital marketing strategies in increasing sales performance across different industry sectors. Using quantitative research methodology, the study analyzed data from 94 customer to identify the most impactful digital marketing approaches and their correlation with sales growth. The research employed structured questionnaires and collected data on social media marketing, content marketing, email campaigns, and SEO optimization efforts. The constant value is 10.513 which means that if there is a Digital Marketing Strategy, the value of Sales Increase is 10.513. This has been described in the simple linear regression test results that there is a direction of relationship between the Digital Marketing Strategy variable (X) and the Sales Increase variable (Y) with positive results that are worth 0.770. Be said that the Digital Marketing Strategy (X) has an effect on Sales Increases (Y)